Online student centred discussion: Creating a collaborative learning environment - Dixon, Robert; Dixon, Kathryn; Axmann, M. (ascilite/Deakin University, 2008)
Many universities both in Australia and overseas are increasingly transferring courses and programs at both graduate and undergraduate level into fully interactive online environments. Online learning and teaching requires different and complimentary skill sets on the part of university teachers. Very little has been documented thus far in regard to training university academics to teach effectively in these environments. This paper investigates the pilot study implementation of the Online Student Centred Discussion Program (OSCD) as designed by Axmann (2006) across the cooperating institutions engaged with Open Universities Australia. The program has been based on Wright and Shoop’s (2003) Student-Centred Discussion Model which places ongoing discussion at the centre of the learning process. The OSCD is designed to develop online protocols, peer- assessment strategies, critical thinking skills as well as promoting collaborative learning through ongoing engagement with online discussion environments. The research reports upon the results of a thirteen item questionnaire which was administered to forty nine participants throughout 2008. The findings indicated that academic staff engaged in learning and teaching online found the OSCD Program to be of value for a number of reasons. The program allowed academics to gain an authentic student experience, something which many of them had forgotten. It also highlighted the varying and different communication patterns and protocols associated with online learning and the development of quite distinct forms of language that are used in this mode of interaction. The research also revealed the need to re-conceptualise the overall instructional design of online learning environments in their own right and not as sub-sets or extensions of traditional face-to face methods of interaction.